Features of airway remodeling in different types of Chinese chronic rhinosinusitis are associated with inflammation patterns. Issue 1 (16th November 2012) - Shi, L‐L.; Xiong, P.; Zhang, L.; Cao, P‐P.; Liao, B.; Lu, X.; Cui, Y‐H.; Liu, Z.
Abstract Background The remodeling patterns in different types of chronic rhinosinusitis (CRS) have rarely been compared, particularly the difference between eosinophilic and noneosinophilic CRS with nasal polyps (CRSwNP). Moreover, whether there is a link between remodeling and inflammation remains controversial. Objective To directly compare the remodeling features of different CRS and to explore their relationship with inflammation in Chinese patients. Methods Histologic characteristics of surgical samples were analyzed in 33 controls, 72 eosinophilic and 76 noneosinophilic CRSwNP, and 72 CRS without nasal polyps (CRSsNP) patients. Tissue samples from 38 controls, 26 eosinophilic and 26 noneosinophilic CRSwNP, and 32 CRSsNP patients were measured for mRNA and/or protein expression of profibrotic growth factors, metalloproteinases (MMPs), tissue inhibitor of metalloproteinases (TIMPs), hypoxia‐inducible factor (HIF)‐1α, interleukin (IL)‐8, eosinophil cationic protein (ECP), and myeloperoxidase (MPO). Results The amount of collagen decreased, whereas the edema scores increased, from CRSsNP to noneosinophilic CRSwNP and to eosinophilic CRSwNP. Transforming growth factor (TGF)‐β2 protein levels were enhanced in CRSsNP compared with CRSwNP. TIMP‐4 protein levels decreased in eosinophilic CRSwNP compared with noneosinophilic CRSwNP and CRSsNP. The number of neutrophils decreased from CRSsNP to noneosinophilic CRSwNP and to eosinophilic CRSwNP. ECP levels were only up‐regulated in eosinophilic CRSwNP. ECP levels and neutrophil number correlated positively with the severity of edema and fibrosis, respectively. Neutrophils were the major sources of TGF‐β2 in CRSsNP and noneosinophilic CRSwNP. Conclusion Distinct remodeling patterns are revealed for different types of CRS, particularly for eosinophilic and noneosinophilic CRSwNP. Tissue remodeling associates with inflammation in CRS.